The role of amniotic epithelial cells in preterm birth: mechanisms and clinical implications - Meng, Lulu; Yang, Jing; Gao, Yijie; Xie, Yiran; Chen, Miaomiao; Hao, Wangping; Luo, Yi; Ru, Ping; Wang, Ling; He, Zhiying; Liu, Ming (Frontiers in Cell and Developmental Biology, 2025)
Preterm birth (PTB), defined as delivery before 37 weeks of gestation, poses a significant global health challenge. This review comprehensively examines the multifaceted role of amnion epithelial cells (AECs) in normal labor induction and preterm birth. AECs, derived from the amniotic ectoderm, exhibit paracrine effects, low immunogenicity, and non-tumorigenicity properties. They contribute to maintaining pregnancy through various aspects, such as immunomodulation, feto-maternal tolerance, and repair of placental membrane microfractures. Disruptions in AEC functions lead to preterm birth through mechanisms involving inflammation, oxidative stress, and the release of proinflammatory cytokines. This review highlights the therapeutic potentials of AECs, particularly in the context of preterm premature rupture of membranes (PPROM) and the related complications. The disruption of AECs has shown promise as a predictive biomarker for preterm birth, whereas AECs as a potential cell therapy have been shown to benefit various neonatal disorders. This review emphasizes the need for further research to fully elucidate the mechanisms underlying the role of AECs in preterm birth and to explore their clinical applications for improving pregnancy outcomes.